KETERWAKILAN PEREMPUAN DALAM KEANGGOTAAN LEGISLATIF DI KABUPATEN SUKOHARJO PROVINSI JAWA TENGAH PERIODE 2019-2024 - Ani Ani Martini; Maichel Wutoy; Perdana Dewi Wardhani (Jurnal Kebijakan Pemerintahan, 2021)
Abstract The minim of support for women becomes one of major obstacle to the fulfillment of 30% representation of women in local legislative. The minim of support influence the work capabilityof women in political institutions. The number of councilors in the Regional House of Representatives of Sukoharjo in the period 2019-2024 is 45 people but only 10 women legislative members or only 22.22% female legislative members so that it has not reached the expectation of 30% female representation in the Regional House of Representatives of Sukoharjo in the period 2019-2024.This shows the representation of women in parliament is low. In fact, political party laws and elections have provided opportunities for women to be able to participate in the politics and enter the legislative. This research is conducted has the find out how women are represented in the Regional House of Representatives of Sukoharjo in the period 2019-2024 and the inhibiting factors that influence and the efforts made to increase women's representation in the Regional Representative Council of Sukoharjo. The theory used is electoral representation theory according to Piktin with four dimensions, namely representative, represented, the substance of representation and context. The method used in the research is a qualitative research method by describing descriptive data and deduktive approaches. Supporting data collection methods in research through observation, interviews, documentation and data triangulation. Data analysis technique used is by reduction of data, display data, and reflecting g conclusion. The research results showed that the representation of women in the the Regional House of Representatives of Sukoharjo in the period 2019-2024 was still low. This is caused by internal factors, namely the confidence of women, social relations, double burden and political costs and external factors, namely patriarchal culture and political constraints and improving the quality of women's resources and encouraging female legislative candidates to establish communication from the start with the community. And efforts to increase the representation of women is improving the quality of the resources of women in politics and encourage female legislative candidates to establish communication from the start with the community. Keywords: feminine representation, regional house of representatives Abstrak Kurangnya dukungan terhadap kaum perempuan menjadi salah satu hambatan belum terpenuhinya kuota 30% keterwakilan perempuan dalam lembaga legislatif. Minimnya dukungan berpengaruh dalam kinerja anggota legislatif perempuan dalam parlemen. Jumlah anggota legislatif di Kabupaten Sukoharjo periode 2019-2024 yaitu 45 orang, tetapi hanya terdapat 10 orang anggota legislatif perempuan atau sekitar 22.22% sehingga belum mencapai harapan 30% keterwakilan perempuan. Hal ini menunjukkan masih minimnya keterwakilan perempuan di parlemen. Padahal, undang-undang dalam pemilu dan partai politik telah memberikan peluang kepada perempuan untuk terjun dalam dunia politik dan berpartisipasi dalam keanggotaan legislatif. Penelitian ini bertujuan untuk mengetahui bagaimana keterwakilan perempuan dalam kenggotaan legislatif Kabupaten Sukoharjo periode 2019-2024 dan faktor penghambat yang mempengaruhi. Teori yang digunakan adalah teori keterwakilan elektoral menurut Pitkin yang terdiri empat dimensi yaitu wakil, yang terwakili, substansi perwakilan dan konteks. Metode yang digunakan dalam penelitian ini merupakan metode penelitian kualitatif dengan menggambarkan data secara deskriptif dan pendekatan secara deduktif. Metode pengumpulan data pendukung dalam penelitian melalui observasi, wawancara, dokumentasi dan triangulasi data. Teknik analisis yang digunakan dengan cara reduksi data, penyajian data dan menarik kesimpulan. Hasil penelitian menunjukan bahwa keterwakilan perempuan dalam keanggotaan legislatif di Kabupaten Sukoharjo periode 2019-2024 masih rendah. Hal ini disebabkan oleh faktor internal yaitu kepercayaan diri dari perempuan, hubungan sosial, beban ganda dan ongkos politik serta faktor eksternal yaitu budaya patriarki dan kendala politik. Upaya yang dilakukan untuk meningkatkan keterwakilan perempuan yaitu meningkatkan kualitas sumber daya perempuan dan mendorong calon anggota legislaif perempuan untuk menjalin komunikasi sejak awal dengan masyarakat. Kata kunci: keterwakilan perempuan, legislatif daerah